2005
DOI: 10.1002/ijc.21003
|View full text |Cite
|
Sign up to set email alerts
|

Bystander signaling between glioma cells and fibroblasts targeted with counted particles

Abstract: Radiation-induced bystander effects may play an important role in cancer risks associated with environmental, occupational and medical exposures and they may also present a therapeutic opportunity to modulate the efficacy of radiotherapy. However, the mechanisms underpinning these responses between tumor and normal cells are poorly understood. Using a microbeam, we investigated interactions between T98G malignant glioma cells and AG01522 normal fibroblasts by targeting cells through their nuclei in one populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 49 publications
2
68
0
Order By: Relevance
“…So far, irradiation with helium particles (Burdak-Rothkamm et al, 2006;Shao et al, 2005;Zhou et al, 2004), soft carbon X-rays , carbon and uranium particles (Fournier et al, 2007) have been used. Again the effect for a given endpoint is estimated from the proportion of irradiated cells and compared to the experimental measurements.…”
Section: Measuring the Bystander Effectmentioning
confidence: 99%
“…So far, irradiation with helium particles (Burdak-Rothkamm et al, 2006;Shao et al, 2005;Zhou et al, 2004), soft carbon X-rays , carbon and uranium particles (Fournier et al, 2007) have been used. Again the effect for a given endpoint is estimated from the proportion of irradiated cells and compared to the experimental measurements.…”
Section: Measuring the Bystander Effectmentioning
confidence: 99%
“…Bystander effects induced by ionizing irradiation have been studied by various approaches including transfer of conditioned medium from irradiated cells (Lyng et al, 2002;Maguire et al, 2005), low particle fluence irradiation, where only a few percent of cells are irradiated (Azzam et al, 1998), and targeted irradiation of single cells and subcellular structures (Shao et al, 2004;Shao et al, 2003bShao et al, , 2005. They have been shown to occur in both tumour and normal cell types.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms involved in bystander signalling have only partially been elucidated and are probably dependent on cell type and end points investigated. The involvement of soluble factors like reactive oxygen species (ROS) (Azzam et al, 2002;Shao et al, 2003aShao et al, , 2005, nitric oxide (NO) (Shao et al, 2003b(Shao et al, , 2005Sokolov et al, 2005) and cytokines released from irradiated cells as well as gap junction intercellular communication (Azzam et al, 2001;Shao et al, 2003a;Mitchell et al, 2004;Sokolov et al, 2005) have recently been reported. Most interestingly, several cytokines can be induced by ROS and NO/NOS (Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004) providing a possible link between different factors potentially involved in bystander signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is accumulating that multiple signal transduction pathways are involved in this process, including oxidative metabolism Shao et al, 2003), gap junction-mediated intercellular communication (GJIC) (Azzam et al, 2001;Ballarini et al, 2002;Wang et al, 2004) and soluble extracellular factors (Iyer and Lehnert, 2000;Little et al, 2002). Earlier studies showed that bystander effects could be induced by treatment of unirradiated cells with medium taken from cell cultures previously exposed to irradiation Seymour, 1997, 1998;Mothersill, 1999, 2000;Lyng et al, 2002).…”
Section: Introductionmentioning
confidence: 99%